NETWORK SYSTEM COMPONENTS AND OBSTACLES ON PT ESSILOR INDONESIA - Mulyadi Mulyadi; Aqwam Rosadi Kardian SKom, MM (Jurnal Sistem Informasi, 2000)
PT ESSILOR INDONESIA in providing services to customers (optical), has beenusing a local network system that supports at-speed service or the ordering process ofthe lens, so that service to customers (optical) is more optimal and can providesatisfaction to the customer.With the existence of this network system, the process of lens orders from ordering todelivery to the customer lens, the more quickly because a customer service receiveorders can quickly inform you go to the warehouse orders. And if there is a customerservice vacancy stock, can deliver more to customers who book early lenses, becausewhen a customer service he received a direct order and then enter the customer'sorder when the input data is completed on the computer immediately notify theamount of the existing stock of types lens ordered by customers, so that a customerservice can know inventory or stock lens without any notification from thewarehouse.